A cross-sectional survey and service evaluation of simple telehealth in primary care: what do patients think?. Issue 6 (28th November 2012) - Cottrell, Elizabeth; McMillan, Kate; Chambers, Ruth
Abstract : Objective: To determine the patient experience of using a simple telehealth strategy to manage hypertension in adults. Design: As part of a pragmatic service evaluation, the acceptability of, satisfaction with and ease of use of a simple telehealth strategy was determined via text, cross-sectional questionnaire survey administered by telephone, case studies, discussion groups and informal feedback from practices. This simple telehealth approach required patients to take home blood pressure (BP) readings and text them to a secure server ('Florence') for immediate automatic analysis and individual healthcare professional review. Participants: 124 intervention patients who used the Florence system. Setting: 10 volunteer general practitioner's (GP) practices in Stoke on Trent, UK, with poor health and high levels of material deprivation took part. Results: Patient satisfaction was high. In particular, patients found the system easy to use, were very satisfied about the feedback from their GP regarding their BP readings, found the advice sent via Florence useful and preferred to send BP readings using Florence rather than having to go to the practice monthly to get BP checked. Overall satisfaction with the system was 4.81/5.00 at week 13 of the programme. Other advantages of being enrolled with Florence were improved education about hypertension, a greater feeling of support and companionship and flexibility which allowed self-care to occur at a time that suited the patient rather than their practice. Conclusions: This simple telehealth strategy for managing hypertension in the community was met with high levels of patient satisfaction and feelings of control and support. This management approach should thus be considered for widespread implementation for clinical management of hypertension and other long-term conditions involving monitoring of patients' bodily measurements and symptoms as a large number of meaningful readings can be obtained from many patients in a prompt, efficient, interactive and acceptable way.